Malaysian heritage food: tourist perception on food culture, knowledge, and lifestyle in Tioman and Perhentian Island - Izhar, Asma Izlyn; Ramli, Norashikin; Mashuri, Mas Affandy; Yildirim, Nur Syazana; Mohd Fisol, Nur Nadia Maisarah; Abu Bakar, Ahmad Redhuan; Johari, Noorsa Riza (Universiti Teknologi Mara Cawangan Pulau Pinang, 2025)
The Malaysian culinary traditions, passed down through generations, have contributed to the global recognition of MHF as a distinctive cuisine. However, the similarities between Malaysian food and that of neighbouring countries underscore the need to strengthen and preserve a culinary identity that is both idealistic and uniquely Malaysian. Nowadays, Malaysian Heritage Food facing modernization and having significant problems maintaining its authentic cultural values. This study examines the relationship between food culture, lifestyle, and tourists’ knowledge in shaping perceptions of MHF in Tioman and Perhentian Islands. Application of quantitative methodology, data sampling was collected via online survey. Random and purposive sampling method yield 351 respondents. Pearson correlation reveal that tourists’ knowledge and lifestyle have strong positive correlations towards perceptions of MHF. Whereas food culture shows a weak and insignificant relationship towards perception of MHF. These results suggest that while cultural heritage remains important, knowledge transmission and lifestyle practices play a more decisive role in sustaining MHF’s appeal. The study highlights the need for educational initiatives, culinary tourism strategies, and policy measures to strengthen the preservation and promotion of MHF in the face of globalization.